Enhancing cybersecurity strategies through future scenarios and strategic thinking : Evidence from the UAE ministry of interior - Aldarmaki, Juma Khalifa Juma Saeed (2025)
Cybersecurity has become a critical concern for governments and organizations as cyber threats continue to evolve, posing risks to national security, financial institutions, and personal data. The UAE Ministry of Interior emphasizes the need for strategic foresight and cybersecurity resilience to mitigate these threats effectively. This study investigates the impact of future scenario planning and strategic thinking on cybersecurity management within the UAE Ministry of Interior, focusing on cyber culture, cyber norms, cyber safety, and cyber engagement. Using a quantitative research approach, data were collected through structured surveys distributed to cybersecurity professionals, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze relationships between key variables. The findings reveal that future scenario planning significantly enhances cybersecurity preparedness by fostering proactive strategies, anticipating risks, and building resilience against emerging cyber threats. Moreover, cyber culture and cyber norms play a crucial role in shaping compliance and security behaviors, while strategic thinking mediates their effectiveness in strengthening cybersecurity frameworks. Organizations with well-defined foresight strategies demonstrated fewer security breaches and improved cyber readiness. This research provides a comprehensive framework for integrating strategic foresight into cybersecurity planning, offering valuable insights for policymakers and cybersecurity professionals. The study recommends enhancing cybersecurity training, fostering a robust cyber culture, and leveraging AI-driven predictive models to mitigate threats proactively. Future research should explore the role of AI and machine learning in cybersecurity scenario modelling to further strengthen national security efforts